Stability analysis for seed yield, its contributing traits and oil content in coriander (Coriandrum sativum L.) - Shah, D P Singh, M A (Journal of Spices and Aromatic Crops, 2003)
Twenty genetically different genotypes of coriander were evaluated for their stability with respect to their seed yield, its contributing traits and oil content. Environments differed significantly as revealed by significant mean square due to environment (linear) for all the traits studied. The genotype x environment interactions was found significant for days to flowering, plant height, 1000 seed weight, harvest index and oil content. Whereas non-significant mean square genotype x environment interaction for remaining traits showed linear response of genotypes to varying environments. Both linear and non-linear interactions were significant for plant height, 1000 seed weight, harvest index and oil content, whereas for seed yield only linear component was significant. The genotypes with good yield potential, average plant height and medium maturity were G.Cori-1, RCr-20, UD-262, RCr-446, UD-744, CS-2, RCr-41 and' G.Cori-2 suited for favourable environment, while Patan mandi-1 and UD-447 with regression coefficient (bi) < 1.0 could be suitable for low yielding environment.